Ekstrak Etanol Daun Mangga (Mangifera indica L.) pada Uji Efektivitas Analgetik Mencit (Mus musculus) - Eri Kurniawan Kardiansyah; Susi Endrawati (Indonesian Journal on Medical Science, 2023)
Mango leaves contain chemical compounds such as alkoloids, flavonoids, steroids, tannins, phenolic acids, flavonols, phenolic esters and mangiferin (C-glucoxanthones). The leaves have properties as a pain reliever. Mangiferin is a substance contained in mango leaves (Mangifera indica L.) which can provide a pain reliever effect. The aim of this study was to examine the ethanol extract of mango leaves (Mangifera indica L.) to test the power of pain relief and determine the levels of extracts that have analgesic effectiveness. The hypothesis that the ethanol extract of mango leaves has the best analgesic effectiveness in mice (Mus musculus). Types of experimental research. The ethanol extract of mango leaves was made in several doses, including 25 mg/kgBB, 50 mg/kgBB, 100 mg/kgBB, the positive control for the analgesic drug was Acetosal 65 mg and the negative control for cooking oil. The results of the observations included the organoleptic test of the extract, the number of stretches that occurred in the test animals after being induced by acetic acid and the percentage of analgesic power. The data analysis technique uses the ANOVA method with the support of the SPSS program. Statistical data from the study showed that the ethanol extract of mango leaves was significantly different from the positive control, namely p value < 0.05. The ethanol extract of mango leaves at doses of 25 mg/kgBB, 50 mg/kgBB, 100 mg/kgBB provided analgetic power of 22.14%, respectively. 22.46%, and 25.31%.